Terpenoid Esters Are the Major Constituents From Leaf Lipid Droplets of Camellia sinensis - Zhou, Xin; Chen, Xiaobing; Du, Zhenghua; Zhang, Yi; Zhang, Wenjing; Kong, Xiangrui; Thelen, Jay J.; Chen, Changsong; Chen, Mingjie (Frontiers in Plant Science, 2019)
Lipid droplets (LDs) have been widely found from diverse species and exhibit diverse functions. It remains unexplored what potential roles they played in tea. To address this question, we analyzed the chemical composition and the dynamic changes of cytosolic LDs during leaf growth and diurnal cycle. Using TopFluor cholesterol and Nile Red staining we demonstrated that cytosolic LDs were heterogeneous in tea tree (Camellia sinensis cv Tieguanyin); the size and number of LDs increased with leaf growth. Compositional analysis showed that terpenoid esters and diacylglycerol are the major components of cytosolic LDs. The contents of total sterol esters (SEs) and β-amyrin esters increased with leaf expansion and growth; individual SE also showed diurnal changes. Our data suggest that cytosolic LDs from tea tree leave mainly serve as storage site for free sterols and triterpenoids in the form of esters. Cytosolic LDs were not the major contributors to the aroma quality of made tea.